2009
DOI: 10.1152/ajpheart.01177.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cyproheptadine prevents pergolide-induced valvulopathy in rats: an echocardiographic and histopathological study

Abstract: Serotonergic drugs, such as pergolide, have been associated with the development of cardiac valvular myxoid thickening and regurgitation in humans and more recently in rats. These effects are potentially mediated by the 5-hydroxytryptamine (5-HT)(2B) receptor (5-HT(2B)R). Therefore, we sought to determine whether cyproheptadine, a 5-HT(2B)R antagonist, might prevent toxic valvulopathy in an animal model of pergolide-induced valvular heart disease. For this purpose, 50 male Wistar rats received daily intraperit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…A general consensus has emerged that 5-HT 2B receptor agonism is the most likely cause of fibrotic valvular heart disease (Roth, 2007;Hutcheson et al, 2011). It has been demonstrated that 5-HT and pergolide-induced valvulopathy in the rat can be prevented by terguride and cyproheptadine, respectively (Hauso et al, 2007;Droogmans et al, 2009). Cyproheptadine is an antagonist with 3-fold higher affinity for 5-HT 2A receptors over 5-HT 2B receptors (Bonhaus et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A general consensus has emerged that 5-HT 2B receptor agonism is the most likely cause of fibrotic valvular heart disease (Roth, 2007;Hutcheson et al, 2011). It has been demonstrated that 5-HT and pergolide-induced valvulopathy in the rat can be prevented by terguride and cyproheptadine, respectively (Hauso et al, 2007;Droogmans et al, 2009). Cyproheptadine is an antagonist with 3-fold higher affinity for 5-HT 2A receptors over 5-HT 2B receptors (Bonhaus et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Un traitement prolongé (cinq mois) par le pergolide comme par la sérotonine induit des lésions valvulaires très proches de celles observées en pathologie humaine tant sur le plan écho-graphique qu'histologique. Sur ce modèle, il a pu être rapporté que l'utilisation d'un antagoniste spécifique des récepteurs 5HT2b, la cyproheptadine, permet de prévenir le développe-ment de la valvulopathie induite par le pergolide [9], ce qui confirme pleinement l'implication de ce sous-type de récep-teurs sérotoninergiques dans l'induction de valvulopathie. On imagine qu'un tel modèle pourrait permettre de prédire le risque de valvulopathie de nouveaux médicaments susceptibles d'interférer avec le système sérotoninergique.…”
Section: Physiopathologie Et Anatomopathologieunclassified
“…CPH is also widely applicable as an H 1 and 5-hydroxytryptamine (5-HT) receptor antagonist for the treatment of allergic reactions, as a prophylactic for migraines and in the symptomatic treatment of metastatic carcinoid syndrome [1]. As a first-generation antihistamine, CPH produces side effects such as sedation and reduced cognitive function [2].…”
Section: Introductionmentioning
confidence: 99%